Neighborhood Socioeconomic Status Affects Patient-Reported Outcome 2 Years After ACL Reconstruction. Issue 6 (25th June 2019) - Jones, Morgan H.; Reinke, Emily K.; Zajichek, Alexander; Kelley-Moore, Jessica A.; Khair, M. Michael; Malcolm, Tennison L.; Spindler, Kurt P.; Amendola, Annunziato; Andrish, Jack T.; Brophy, Robert H.; Flanigan, David C.; et al.
Background: Lower socioeconomic status (SES) is associated with worse patient-reported outcome (PRO) after orthopaedic procedures. In patients with anterior cruciate ligament (ACL) reconstruction, evaluating SES by use of traditional measures such as years of education or occupation is problematic because this group has a large proportion of younger patients. We hypothesized that lower education level and lower values for SES would predict worse PRO at 2 years after ACL reconstruction and that the effect of education level would vary with patient age. Purpose: To compare the performance of multivariable models that use traditional measures of SES with models that use an index of neighborhood SES derived from United States (US) Census data. Study Design: Cohort study; Level of evidence, 3. Methods: A cohort of 675 patients (45% female; median age, 20 years), were prospectively enrolled and evaluated 2 years after ACL reconstruction with questionnaires including the International Knee Documentation Committee (IKDC) questionnaire, the Knee injury and Osteoarthritis Outcome Score (KOOS), and the Marx activity rating scale (Marx). In addition, a new variable was generated for this study, the SES index, which used geocoding performed retrospectively to identify the census tract of residence for each participant at the time of enrollment and extract neighborhood SES measures from the 2000 US Census Descriptive Statistics. Multivariable models were constructed that included traditional measures of SES as well as the SES index, and the quality of models was compared through use of the likelihood ratio test. Results: Lower SES index was associated with worse PRO for all measures. Models that included the SES index explained more variability than models with traditional SES. In addition, a statistically significant variation was found regarding the impact of education on PRO based on patient age for the IKDC score, the Marx scale, and 4 of the 5 KOOS subscales. Conclusion: This study demonstrates that lower neighborhood SES is associated with worse PRO after ACL reconstruction and that age and education have a significant interaction in this patient population. Future studies in patients who have undergone ACL reconstruction should attempt to account for neighborhood SES when adjusting for confounding factors; further, targeting patients from areas with lower neighborhood SES with special interventions may offer an opportunity to improve their outcomes.